Neutrophil Count Predicts Malignant Cerebellar Edema and Poor Outcome in Acute Basilar Artery Occlusion Receiving Endovascular Treatment: A Nationwide Registry-Based Study - Liu, Chang; Li, Fengli; Liu, Shuai; Chen, Qiong; Sang, Hongfei; Yang, Qingwu; Zhou, Kai; Zi, Wenji (Frontiers in Immunology, 2022)
Background: Acute basilar artery occlusion(ABAO) stroke is known to have poor outcome with a high rate of morbidity and mortality despite endovascular treatment(EVT), highlighting the necessities of exploring factors to limit the efficacy of EVT in these patients. Cerebellar infarctions in ABAO might progress to malignant cerebellar edema(MCE), a life-threatening complication after reperfusion posing secondary injury to brainstem by mass effects. Therefore, present research aimed to explore impacts of MCE on long-term outcome, and investigate prognostic factors for MCE among ABAO after EVT. Methods: In national BASILAR registry, a total of 329 ABO patients with cerebellar infarctions treated by EVT met inclusion criteria. The presence of MCE defined by Jauss scale≥4 points, was evaluated on the computed tomography performed 72 hours after EVT. Adjusted odds ratio and 95% CI were obtained by logistic regression models. A favorable outcome was defined as a 90-day modified Rankin Scale score of 0–3. Results: MCE was statistically associated with decreased incidence of favorable outcome (adjusted odds ratio, 0.35[95% CI, 0.18-0.68], P=0.002). Baseline NIH Stroke Scale score, collateral circulation, neutrophil count at admission and recanalization status were predictors for MCE and favorable functional status at 90 days (all P<0.05). Among all inflammatory factors, neutrophil count achieved the highest accuracy, sensitivity, and specificity for MCE. Adding neutrophil count status into the baseline model obviously enhanced its prediction ability for MCE and favorable outcome by increasing area under curve, and achieving both net reclassification and integrated discrimination improvement(all P<0.05). Mediation analysis indicated that MCE mediated the association between increased neutrophil count and worse functional outcome(P=0.026). Discussion: MCE acted essential roles in worsening prognosis for ABAO after EVT. High neutrophil count at admission was linked to MCE and poor outcome among ABAO patients, which could be further incorporated into the clinical decision-making system and guide immunomodulation therapy.